How Code Smell and Refactoring Affect the Software Product Line Maintainability - Maryam Mehmood; Asad Ijaz (Journal of Computing Innovations and Emerging Technologies, 2025)
Code cloning remains a significant challenge in modern software development, particularly within the Object-Oriented paradigm and advanced methodologies such as the Software Product Line (SPL) approach. In this context, code smells and refactoring can be seen as two sides of the same coin—one representing the symptoms of poor design, and the other offering systematic strategies for improvement. Among the various software quality attributes, maintainability stands out as a critical factor in determining the long-term success of SPL-based systems. However, the presence of cloned code directly impacts this maintainability, making the detection and mitigation of such clones an essential concern. Although multiple quality models exist to assess the relationship between code cloning, refactoring, and maintainability, most lack the granularity to accurately capture the specific effects of code cloning within SPL environments. This research undertakes a systematic literature review to consolidate and analyze findings from existing surveys, with a particular focus on identifying software metrics capable of evaluating the impact of refactoring on SPL maintainability. Refactoring serves as a deliberate means to eliminate code smells, and numerous tools and techniques have been developed to support this process. By synthesizing the current body of knowledge, this study provides a foundation for researchers and practitioners to better understand, select, and apply effective practices and tools to reduce code smells, improve maintainability, and ultimately enhance the overall quality of SPL-based software systems